2018
DOI: 10.1139/apnm-2017-0648
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacilli and bifidobacteria ameliorate memory and learning deficits and oxidative stress in β-amyloid (1–42) injected rats

Abstract: The gastrointestinal microbiota affects brain function, including memory and learning. In this study we investigated the effects of probiotics on memory and oxidative stress biomarkers in an experimental model of Alzheimer's disease. Sixty rats were randomly divided into 5 groups: control; control-probiotics, which received probiotics for 8 weeks; sham operation, which received an intrahippocampal injection of phosphate-buffered saline; Alzheimer, which received an intrahippocampal injection of β-amyloid (Aβ1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(90 citation statements)
references
References 43 publications
3
86
0
1
Order By: Relevance
“…First reports indicate successful application in animal models: Lactobacillus plantarum, for example, was able to restore cognition and levels of acetylcholine esterase in the brain of a D-galactose-evoked AD-like rat model [94]. Similar results were obtained from investigations using genetic AD mouse models with Bifidobacterium breve strain A1 [95], SLAB51 (probiotic formulation, [96]) but also with Lactobacillus acidophilus, Lactobacillus fermentum, Bifidobacterium lactis, and Bifidobacterium longum in rodent sporadic AD models due to amyloid-β injection [97][98][99]. As only one explorative intervention study reports on a small cohort of AD human patients [100], the usefulness in humans is still not proven.…”
Section: Therapeutic Strategies Derived From Microbes Against Human Asupporting
confidence: 67%
“…First reports indicate successful application in animal models: Lactobacillus plantarum, for example, was able to restore cognition and levels of acetylcholine esterase in the brain of a D-galactose-evoked AD-like rat model [94]. Similar results were obtained from investigations using genetic AD mouse models with Bifidobacterium breve strain A1 [95], SLAB51 (probiotic formulation, [96]) but also with Lactobacillus acidophilus, Lactobacillus fermentum, Bifidobacterium lactis, and Bifidobacterium longum in rodent sporadic AD models due to amyloid-β injection [97][98][99]. As only one explorative intervention study reports on a small cohort of AD human patients [100], the usefulness in humans is still not proven.…”
Section: Therapeutic Strategies Derived From Microbes Against Human Asupporting
confidence: 67%
“…The presence of a gut–brain axis modulating dementia physiopathology was first demonstrated with the circumstance that urolithins, gut microbiota-derived metabolites from grape seed ellagitannins, can improve β-amyloid aggregation and signs of cognitive impairment in animal models 80,81. Then, the administration of other prebiotics, including teasaponin, fructo-oligosaccharides, baicalein and xylo-oligosaccharides, proved effective in preventing the advancement of cognitive symptoms in mouse models of AD or vascular dementia 79,8284…”
Section: Resultsmentioning
confidence: 99%
“…Probiotics are live microorganisms intended to provide health benefits, generally by improving or restoring the GM [22][23][24]49]. Moreover, Athari Nik AGING Azm et al [50] pointed out that reduction in the number of amyloid plaques, inflammation and oxidative stress were observed in an Alzheimerprobiotics group. Kobayashi et al [51] also revealed that probiotics administration suppressed hippocampal gene expression of inflammation and oxidative stress related genes in an AD mouse model.…”
Section: Discussionmentioning
confidence: 99%